Software "Modellus" e modelagem matemática: relacionando conceitos matemáticos com fenômenos da física - Barcelos, Sérgio Renato (2017)
This research presents an application and analysis of Modellus Software in the ninth grade of Elementary School, associated with practical activities involving Kinematics, which started from a problem of reality suggested by the students. The mathematical subject is about functions, presenting general and essential concepts, developing models from physical problems and study of tables and graphs. The investigated problem was: Does the use of the computational resource Modellus help in the teaching-learning process of the functions concept? The subjects were developed aiming to allow the researched student relate the content with their daily life. The Modellus Software was chosen for the possibility of the student interacting with the development of graphics, animations and tables from mathematical models. The conclusions of the research were obtained by analyzing the activities carried out, evaluations and diagnostic questionnaires. We sought to base these considerations with the presentation of results generated by the students to assert that the Software Modellus allowed a differentiated learning, in which the student interacted with the knowledge construction regarding to the subject functions. It was concluded that the Modellus Software was adequate for the teaching of functions with this class of ninth grade from the data analyzed in this dissertation.